Going for Hybrid Crops Breeding in Nepal: Strategies and Policy Dimensions - Tiwari, Khusi Ram; Panthee, Dilip Raj; Joshi, Bal Krishna; Subedi, Kalidas (Nepal Public Policy Review, 2023)
Crop Breeding programs were initiated in Nepal in 1951 with a focus on the varietal improvement of cereal crops. These varieties, however, have limited impact in the farmers’ field due to their low adaptation and low yield potentials. Nepal annually imports hybrid seeds of cereals, vegetables, and flowers from India, China, and elsewhere costing billions of Rupees. It is estimated that approximately 73% of the vegetable seeds and over 60% of the hybrid seeds of maize and rice are imported annually. Hybrid seeds generally produce 20-25% more yield than conventional varieties. Despite this fact, only about 15% of maize and <10% of rice acreage in Nepal has hybrid seeds compared to over 50-60% in China. Nepal is behind in developing policies for genetic innovations, including genetics and breeding, utilizing genetic diversity, and using new biotechnological traits such as golden rice and drought tolerant wheat which could be important for Nepal in the future. Nepal has the technical knowledge, skilled human resources, and appropriate environment to produce hybrid and improved seeds of most of the crops in Nepal, but there is a lack of proper policies in place. Nepal can learn lessons from our neighboring countries, including India, China, Philippines, and Bangladesh, which are highly engaged in new technology of crop genetics, hybrid breeding, proper Plant Variety Protection (PVP) laws, and private-sector entrepreneurship. In addition, Nepal should aim to be self-sufficient and export quality hybrid seeds of cereals and vegetables that can be produced in its diverse geographies and production niches.